Pengaruh Kepuasan Kerja dan Motivasi Kerja Terhadap Perilaku Organisasi Karyawan pada UMKM d’SRUPUT Lubuk Begalung Padang - Okkyramdhany; Raisha Andriani; Rian Hidayat; Risco Daffa Ramli; Vivi Nila Sari (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to investigate the impact of job satisfaction and work motivation on employee organizational behavior at UMKM d'SRUPUT Lubuk Begalung Padang. Job satisfaction and work motivation are seen as internal factors that can influence how employees interact and contribute in the context of small and medium organizations. The research results show that there is a positive relationship between job satisfaction and work motivation and employee organizational behavior. This means that the higher the level of job satisfaction and work motivation of employees, the better the organizational behavior shown by them at UMKM d'SRUPUT Lubuk Begalung Padang. The implication of this research is that it is important for MSME management to pay attention to these internal factors in an effort to improve overall organizational performance.